Description and management of retinopathy of prematurity reactivation after intravitreal antivascular endothelial growth factor therapy. Issue 5 (September 2021) - Valikodath, Nita G.; Chiang, Michael F.; Chan, R.V. Paul
Abstract : Purpose of review: To review the literature regarding reactivation of retinopathy of prematurity (ROP) after treatment with antivascular endothelial growth factor (anti-VEGF) agents. Recent findings: Reactivation can occur after anti-VEGF or laser. Risk factors for reactivation include patient and disease-related factors. Various studies are evaluating the use of different anti-VEGF agents and reactivation rates. However, the definition of reactivation varies between studies. Summary: The literature has varied definitions of reactivation, which is often used interchangeably with recurrence. It is important to recognize features of reactivation of ROP to appropriately manage patients and conduct clinical trials. The International Classification of ROP 3 rd edition has established a consensus guideline regarding terminology describing reactivation.